Exploring e-Commerce Potential: Improving Sales Performance Through Product Innovation in The Agriculture Sector - Macoa Gau, Andi; Saleh, Nursahdi (Jurnal Economic Resource, 2024)
This study explores the impact of e-commerce on sales performance, mediated by innovation, among agricultural business entrepreneurs in Polewali Mandar, West Sulawesi Province. Utilizing a quantitative research design, data were collected from 97 agricultural entrepreneurs who have adopted technology in their sales processes. The study employs WarpPLS 8.0 for data analysis to test the hypothesized relationships between e-commerce, innovation, and sales performance. Results indicate that e-commerce significantly enhances sales performance both directly (path coefficient = 0.727, p < 0.001) and through innovation (path coefficient = 0.207, p = 0.001). Additionally, e-commerce positively impacts innovation (path coefficient = 0.901, p < 0.001), and innovation itself significantly boosts sales performance (path coefficient = 0.230, p < 0.001). These findings corroborate prior research, underscoring the importance of effective resource management, strategic goal alignment, and employee competencies in improving sales outcomes. Advanced technologies, such as machine learning, further enhance businesses' ability to predict and optimize sales strategies. For agribusiness entrepreneurs in Polewali Mandar, the study highlights the necessity of embracing digital transformation. Despite initial skepticism, the integration of e-commerce platforms and innovative marketing strategies can expand market reach, improve operational efficiency, and build consumer trust. This research provides practical recommendations for leveraging digital technologies to drive growth and profitability. By focusing on consistent and relevant digital content, agribusinesses can overcome barriers and achieve sustainable competitive advantages. The findings underscore the critical role of digital and technological innovations in fostering business success in the agricultural sector.